Fetal Conduction Disease and Arrhythmia in Ebstein's Anomaly and Tricuspid Valve Dysplasia Assessed by Fetal Magnetocardiography - Annette Wacker‐Gussmann; Gabriela Tardelli; Bettina F. Cuneo; Janette F. Strasburger; Ronald T. Wakai (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Ebstein's anomaly and tricuspid valve dysplasia are associated with perinatal mortality approaching 50% and are among the most difficult fetal conditions to manage. Prediction of perinatal mortality is difficult and remains an active area of research. The usefulness of electrophysiologic indicators has not been investigated. Methods Eighteen fetuses with a diagnosis of Ebstein's anomaly and tricuspid valve dysplasia were referred for fetal magnetocardiography evaluation. We assessed fetal rhythm, waveform intervals, and heart rate variability and reactivity. Results Two subjects were lost to follow‐up and 1 remains in utero. Of the other 15, 6 (40%) did not survive: 5 died within the first month of life, and 1 died at 4 months following surgery. Compared with normal fetuses, the Ebstein's anomaly and tricuspid valve dysplasia group exhibited significantly prolonged P‐wave duration (P <0.01), PR interval (P <0.03), and QRS duration (P <0.01), along with an increased P/QRS amplitude ratio (P <0.01). The most prominent fetal magnetocardiography abnormalities included tall, broad P‐waves suggestive of atrial enlargement and markedly prolonged QRS complexes consistent with bundle branch block. Of the 6 nonsurvivors, 4 had QRS durations ≥90 milliseconds (Z >4), and 4 demonstrated impaired atrioventricular conduction, including PR prolongation and second‐degree atrioventricular block. Additionally, 4 showed absent heart rate variability and minimal reactivity. Abnormal findings were more prevalent in the third trimester than earlier in gestation. Conclusions Ebstein's anomaly and tricuspid valve dysplasia manifests distinct conduction and rhythm abnormalities detectable by fetal magnetocardiography but not by echocardiography. These electrophysiologic markers were associated with perinatal mortality and may serve as useful prognostic indicators. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT03047161.